Порошки для изготовления керамики: учебное пособие - Лямина Г. В. Галина Владимировна; Качаев А. А. Артем Алексеевич; Божко И. А. Ирина Александровна; Годымчук А. Ю. Анна Юрьевна; Воронова Г. А. Гульнара Альфридовна; Панина А. А. Александра Анатольевна; Бикбаева З. Г. Зульфа Гадильзановна (Томск, Изд-во ТПУ, 2014)
Заглавие с титульного экрана